Will Boys Always Be Boys? The Criminalization of Street Harassment in Portugal - Ribeiro, Beatriz C. (Violence against women, 2024)
Albeit one of the most pervasive forms of gender violence, street harassment tends to be either not considered a crime or to be faulty criminalized. This investigation contributes to better understand the overall inefficiency of existing laws through an analysis of the criminalization of street harassment in Portugal. Particularly, it searches for obstacles to implementation among those responsible for the process—the street-level bureaucrats of the Portuguese Public Security Police. Through 14 semi-structured interviews, three groups of obstacles to implementation were identified: perceptions of the legislation's content, a masculinist institutional culture, and personal characteristics. These are new findings that contribute to an understanding of the perpetuation of gender violence through state's institutions and workers.